(untitled) - Hamilton, Angus (Boston, 1910)
This book introduce about the orenburg - Tashkent railway, the Khanate of Bokhara, the province of Samarkand, the district of Merv, from Tashkent to Merv, the northern border, the murghab valley railway...
Keywords: Afghanistan,Afghanistan; Lịch sử,History